Experimental investigation of the ease allowance of clothing and thermal-moisture comfort in exercise based on fuzzy comprehensive evaluation - Zhang, Jun; Tong, Mengxia; Zhang, Mengyun; Zhang, Yating; Jiang, Xuewei; Zhu, Xiaoxiao; Guo, Mengna (Journal of engineered fibers and fabrics, 2024)
The level of thermal-moisture comfort experienced by an individual is strongly influenced by the clothing they wear and also influenced by the ease allowance of that clothing. This study aimed to investigate the impact of ease allowances of clothing on thermal-moisture comfort during exercise or movement. Seventeen female subjects were asked to wear sample clothing with different sizes during a designated 5-phase exercise in a climate chamber. Throughout the exercise phases, the temperature and humidity of the microclimate under the clothing were monitored while the subjects provided subjective evaluations of their comfort levels. To account for variation in ease allowances, the 32 experimental repetitions were grouped based on the ease allowance of the clothing worn. The FCE-CRITIC method was then used to determine the variable weights of factors and to compare the thermal-moisture status to the subjective evaluation. Results revealed that humidity was more strongly weighted during RS and RC (i.e., running and recovery phase after exercise) compared to other phases, means that moisture comfort was the main factor driving the clothing comfort sensation within the two phases. The ease allowance of clothing was found to have an impact on the sensations of thermal and moisture comfort during exercise, although this effect was not significant. Furthermore, the study identified the optimum range of ease allowance for thermal-moisture comfort during exercise to be between 6 and 10 cm.